ETIKA KOMUNIKASI DALAM KOMENTAR NETIZEN DI YOUTUBE: Studi Etnografi Virtual pada Konten Live Sidang Ijazah Palsu Berlanjut Rocky Gerung Jadi Saksi Ahli di Youtube Refly Harun dan Konten Refly Harun Mencium Bau Intimidasi Soal Gugatan Penundaan Pemilu 2024 di YoutubetvOneNews - Sapari, Yusuf; Suhara, Rizki Budhi; Riaeni, Ida; Suherman, Suherman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2024)
Advances in technology and the internet have not only given rise to new media but have become a human need to interact and socialize, one of which is communication technology innovation in the form of social media. With social media that can be accessed by the wider community, people in villages and cities also get the same information about education, technology, knowledge and so on. The development of the use of social media as a means of communication is increasingly rapid after the internet can be accessed via cell phones, even now people can access it anytime, anywhere using a smartphone or the term gadget has emerged which makes it easier for people to access it anywhere and anytime without any time limits. Good communication ethics in consuming social media and in accordance with Islamic teachings are not to use harsh words, pornography, or